Curso de Pedagogia de Rio Claro - Maria Cecília de Oliveira Micotti (Universidade Estadual Paulista Júlio de Mesquita Filho, 2007)
This article discribes some historical phases of higher Educational studies, particularly the studies of Pedagogy, in Rio Claro SP., Brazil. Attention has chiefly focused on the curriculum organization and changes.